MENINGKATKAN MENGENAL BENTUK GEOMETRI MELALUI KEGIATAN FUN COOKING PADA ANAK USIA 4-5 TAHUN DI PAUD-IT BUNAYYA PEKANBARU - Fitriani Fitriani; Tri Umari; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research objective was to determine the use of fun cooking in enhancing the ability to recognize shapes of geometry in children aged 4-5 years in early childhood - IT Bunayya Pekanbaru, to improve the ability to recognize shapes of geometry in children aged 4-5 years through fun cooking activity in early childhood - IT Bunayya Pekanbaru, To find an increase in the ability to recognize shapes of geometry in children aged 4-5 years through fun cooking activity in early childhood - IT Bunayya Pekanbaru. Based on the results of a classroom action research that has been done, it can be concluded that the ability to know the geometry of children aged 4-5 years in early childhood-IT Bunayya increased in each cycle. This is evident from the acquisition value of the average pre-Cycle 44.58%, 54.44% the first cycle, and the second cycle 80.55%, Implementation fun cooking activities conducted in two cycles. Each cycle consisted of three meetings, Improved ability to recognize geometric shapes from the pre cycle to cycle II increased by 80.68%Key Word: Geometric Shapes, Fun Cooking